PENGARUH TENAGA KERJA, MODAL DAN TEKNOLOGI TERHADAP PRODUKSI DAN PENDAPATAN PENGERAJIN INDUSTRI KERAJINAN SEMAT - I Nyoman Mahaendra Yasa, Ida Ayu Nyoman Putri Hartati (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Bangli Regency is a district with the largest number of woven bamboo, rattan and the like handicraft industries in Bali Province, one of which is the semit handicraft industry. Most of the semin handicraft industry is in Tembuku District, precisely in Bangbang Village. The data used is in the form of primary data collected from sources spread across three banjars, namely Banjar Cepunggung, Banjar Bangkiang Sidem and Banjar Bangbang Kaja. The samples of this research were 56 units from 64 populations of the semat handicraft industry which were taken by simple random sampling technique. The analysis technique used is path analysis and single test. The purpose of this study was to analyze the effect of labor, capital and technology on the production and income of craftsmen in the metal craft industry in Bangbang Village, Tembuku District, Bangli Regency. The results showed that Labor and Capital had a positive and significant direct effect on production, while Modern Technology provided greater production than traditional technology for craftsmen in the semit craft industry. Labor, Capital and Production have a positive and significant effect directly on income, while Modern Technology provides higher income than traditional technology for craftsmen in the semit craft industry. Labor, Capital and Technology have an indirect effect on income through the production of craftsmen in the semat handicraft industry in Bangbang Village.